ANALISIS REALISASI ANGGARAN BELANJA PEGAWAI DI DINAS PERTANIAN KABUPATEN GORONTALO - Yusuf, Fitria Melynsyah; Ali, Yuwin; Saputro Djahuno, Nur Iman (Program Studi Akuntansi, 2024)
This research aims to analyze the realization of employee expenditure budgets based on the Regulation of the Minister of Finance of the Republic of Indonesia Number 102/PMK.02/2018 concerning the classification of employee expenditure budgets at the Gorontalo Regency Agriculture Service. This research uses descriptive qualitative methods with observation techniques, documentary interviews and triangulation. The results of this research conclude that the realization of the Employee Expenditure Budget is based on Minister of Finance regulations. So, with the management of allowances, protection and increasing regional income which causes silpa, the remaining budget is then allocated in the following year